A Study on Implementation of Inclusive Education at the Elementary Level in the selected North-Eastern States - Kharlukhi, Basansy (INDIAN EDUCATIONAL REVIEW, 2016)
The north-east India, the eastern most region of the country, is connected with the mainland through a narrow corridor squeezed between Nepal and Bangladesh. It comprises eight states and the location of the region is strategically important as it has international borders with Bangladesh, Bhutan, China, Myanmar and Tibet. The present system of education in the north east India started in the early years of the nineteenth century with the coming of the Christian missionaries who came as traders. According to the 2011 census, the total literacy rate in the region stands at 68.5 percent.